Analysis of A Tall Structure Considering Opening Wall Conditions Using ETABS - Ahirwar, Varsha; Sathbhiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2023)
Shear walls are structural systems which provide stability to structures from lateral loads like wind, seismic loads. An attempt is made to apply the finite element modelling in analyzing and exploring the behavior of shear wall with opening under seismic load actions. Shear walls are generally located at the sides of buildings or arranged in the form of core that houses stairs and lifts. The properties of these seismic shear walls dominate the response of the buildings, and therefore, it is important to evaluate the seismic response of the shear walls appropriately. Due to functional requirements such as doors, windows, and other openings, a shear wall in a building contains many openingsIn this research, the main focus is to determine effectiveness of shear wall with vertical opening and staggered opening in regular and irregular buildings under earthquake loads with the help of finite element software, ETABS. using the Response Spectrum method. The comparative results showed that the time period, displacement, base shear and stress distribution around the openings depend on the arrangement of openings. Finally, the staggered arrangement of openings in shear walls is suggested to be applied in practice, since it satisfies both the architectural and the seismic requirements.
Keywords: ETABS; Seismic behavior; Storey drift; Shear Wall; Staggered Openings; Seismic Loads; Finite Element Analysis; Response Spectrum Method